Existence and subharmonicity of solutions for nonsmooth $ p $-Laplacian systems - Ning, Yan; Lu, Daowei; Mao, Anmin (AIMS mathematics, 2021)
In this paper we study nonlinear periodic systems driven by the vectorial $ p $-Laplacian with a nonsmooth locally Lipschitz potential function. Using variational methods based on nonsmooth critical point theory, some existence of periodic and subharmonic results are obtained, which improve and extend related works.